2015
DOI: 10.4067/s0717-95022015000400011
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Immunohistochemical Identification of Villous M Cells in the Small Intestine of Newborn Piglets

Abstract: SUMMARY: Microfold (M) cells act as antigen-sampling sites for initiating antigen specific mucosal immune responses, but they may also provide a gateway for enteropathogen entry. In this study we demonstrated villous M cells by morphological and immunohistochemical methods to be present in the three regions of the small intestine from newborn piglets. Immunohistochemical analysis, using anti-cytokeratin 18 (CK18) primary antibodies, showed a gradually decreased density of M cells from the lower crypt epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The transmission electron microscopy revealed less electron-dense cytoplasm containing abundant mitochondria, lysosomes and small vesicles with few secretory granules. The present findings had a close resemblance to the findings of Renfeng et al [43] in piglets. In the present study, the differences in M-cells between control and treatment group piglets could not be made due to constraints in enough exposure availability of transmission electron microscopy.…”
Section: Discussionsupporting
confidence: 92%
“…The transmission electron microscopy revealed less electron-dense cytoplasm containing abundant mitochondria, lysosomes and small vesicles with few secretory granules. The present findings had a close resemblance to the findings of Renfeng et al [43] in piglets. In the present study, the differences in M-cells between control and treatment group piglets could not be made due to constraints in enough exposure availability of transmission electron microscopy.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the evaluation of in vivo M cells from mouse Peyer's patches also presented similar results with the appearance of unique morphological structure with lack, blunted and shorter microvilli [6,18,19]. The same characteristic of microvilli was also observed on the small intestine of the newborn piglets, whereby the villous M cells showed depressed, short stub-like microvilli as compared to enterocyte epithelium [20].…”
Section: Discussionsupporting
confidence: 60%
“…M‐cells are highly heterogeneous in proportion and phenotype among the different species (Brayden & Baird, ) and various histochemical markers for their detection have been established (Casteleyn et al, ; Renfeng et al, ). Earlier, Kumar et al () identified M‐cells in the FAE of the equine nasopharyngeal tonsil on the basis of short microvilli, an intimate association with lymphocytes, cytoplasmic vimentin filaments and epitopes on the apical surface reactive with lectin GS‐1‐B4 specific for α‐linked galactose.…”
Section: Resultsmentioning
confidence: 99%